Lateral Torsional Buckling of Wood Beams - Xiao, Qiuwu (Université d'Ottawa / University of Ottawa, 2014)
Structural wood design standards recognize lateral torsional buckling as an important failure mode, which tends to govern the capacity of long span laterally unsupported beams. A survey of the literature indicates that only a few experimental programs have been conducted on the lateral torsional buckling of wooden beams. Within this context, the present study reports an experimental and computational study on the elastic lateral torsional buckling resistance of wooden beams. The experimental program consists of conducting material tests to determine the longitudinal modulus of elasticity and rigidity modulus followed by a series of 18 full-scale tests. The buckling loads and mode shapes are documented. The numerical component of the study captures the orthotropic constitutive properties of wood and involves a sensitivity analysis on various orthotropic material constants, models for simulating the full-scale tests conducted, a comparison with experimental results, and a parametric study to expand the experimental database. Based on the comparison between the experimental program, classical solution and FEA models, it can be concluded that the classical solution is able to predict the critical moment of wood beams. By performing the parametric analysis using the FEA models, it was observed that loads applied on the top and bottom face of a beam decrease and increase its critical moment,respectively. The critical moment is not greatly influenced by moving the supports from mid-span to the bottom of the end cross-section.
Keywords: full-scale tests; FEA models; lateral torsional buckling